Les représentations zoomorphes du PPNA et du PPNB au nord du Proche-Orient - Tomasso, Sonja (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The Pre-Pottery Neolithic sites in the north of the Middle East, to be more specific in the Middle Euphrates valley and the high valleys of the Tigris-Euphrates basin, show the prominent role of animal representations in this area. The symbolism is often very diverse and represented on a large number of different relics. The iconographic landscape is furthermore very heterogeneous. Wide variability of representations leads us to believe that this is a result of a profound knowledge of the regional wilderness. The artistic representations do not provide an illustrated guide to local wildlife. Furthermore, they do not show the real impact different species had in the economy. Numerous studies provided evidence on that. It is rather a limited repertoire, of which the wildlife makes the essential part. Everything indicates that the choice of animals is done in a very conscious way. After analyzing all of these aspects, we will propose some interpretations based on previous studies about the specifi c choices made within the presence of animals, the symbolic frames that could underlie these choices and other possible reasons that could have led to these presentations.